Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) of Tropical Asia, with the Description of a New Species - Sanoamuang, La-Orsri (Zool Stud, 2020)
We describe a new species of Eulimnadia from the Oriental region using museum specimens collected from India and fresh material from Thailand. This species has egg morphology resembling E. magdalensis s. lat. and E. chaperi, but distinctly differs from them by presence of a narrow depression at the polygon floor. We also comment on the species status of E. khoratensis from Thailand based on egg morphology, and present a taxonomic key for identification of tropical Asian species of Eulimnadia.